2017
DOI: 10.1055/s-0037-1601449
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Phenotypic, and Interferon Biomarker Status in ADAR1-Related Neurological Disease

Abstract: We investigated the genetic, phenotypic, and interferon status of 46 patients from 37 families with neurological disease due to mutations in ADAR1. The clinicoradiological phenotype encompassed a spectrum of Aicardi–Goutières syndrome, isolated bilateral striatal necrosis, spastic paraparesis with normal neuroimaging, a progressive spastic dystonic motor disorder, and adult-onset psychological difficulties with intracranial calcification. Homozygous missense mutations were recorded in five families. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 28 publications
3
115
0
1
Order By: Relevance
“…Exome sequencing revealed compound heterozygous pathogenic ADAR variants c.577C>G;p.Pro193Ala (paternally derived) and c.3202+1G>A (maternally derived), as previously reported 9. The p.Pro193Ala substitution represents the most frequent pathogenic variant in ADAR so far identified,10 while the canonical splice-site variant is not recorded in control databases (https://gnomad.broadinstitute.org/).…”
Section: Case Reportssupporting
confidence: 69%
“…Exome sequencing revealed compound heterozygous pathogenic ADAR variants c.577C>G;p.Pro193Ala (paternally derived) and c.3202+1G>A (maternally derived), as previously reported 9. The p.Pro193Ala substitution represents the most frequent pathogenic variant in ADAR so far identified,10 while the canonical splice-site variant is not recorded in control databases (https://gnomad.broadinstitute.org/).…”
Section: Case Reportssupporting
confidence: 69%
“…The consequences of altered ADAR1 function are severe, from embryonic lethality in mice to debilitating neurological disease and systemic interferonopathy in humans with loss-of-function alleles [ 22 , 52 ], to putative oncogenic roles when overexpressed [ 31 , 53 , 54 ], so it is critical to clearly define the key function(s) of ADAR1. In contrast to the physiologically essential role of transcript recoding by ADAR2, the importance of recoding to the biology of ADAR1 was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mice homozygous for a single amino acid substitution resulting in an editing-deficient ADAR1 protein ( Adar1 E861A/E861A ) die at E13.5, with remarkably similar phenotypes to the null allele [ 19 ]. Activation of the innate immune sensing system, termed an interferonopathy, is observed in the subset of Aicardi-Goutières syndrome (AGS) patients who harbor mutations in ADAR , demonstrating that the transcriptional response to loss of ADAR1 activity is conserved across mammals [ 17 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in mouse showed that ADAR is implicated in erythropoiesis [67;68]. ADAR heterozygous mutations are been found in dyschromatosis symmetrica hereditaria [69] and homozygous or compound heterozygous variations in Aicardi-Goutières syndrome [70].…”
Section: Discussionmentioning
confidence: 99%